Alfaz al-Qur’an al-karim al-muqtaradhah fi al-lughah al-Malayuwiyyah: dirasah tahliliyyah fi al-Juz’ al-thalatheen - Chik, Abdul Rahman; Ibrahim, Roi Ibrahim (IRKHS, IIUM, 2021)
Quranic loan words in Malay language, an analysis on Juz (chapter) no. 30.